SAT0155 Adalimumab in combination with non-methotrexate conventional synthetic disease modifying rheumatic drugs in a clinical trial setting. (15th June 2017) - Keystone, EC; Suboticki, J; Griffith, J; Zhang, Y; Kremer, JM
Abstract : Background: Biologics in combination with methotrexate (MTX) are associated with improved outcomes versus monotherapy. However, few data exist regarding the use of non-MTX conventional synthetic disease modifying rheumatic drugs (csDMARDs) with biologics. Objectives: To assess the effectiveness and safety of adalimumab (ADA) in combination with MTX and non-MTX csDMARDs through 6 months. Methods: This post hoc analysis used data from the 24-week (wk) placebo-controlled trial of ADA (STAR), assessing safety and efficacy of ADA+csDMARDs in patients (pts) with moderate to severe RA. 1 For those pts receiving 1 csDMARD, pts were subgrouped according to csDMARD. The most frequently used csDMARDs assessed were MTX, sulfasalazine (SSZ), hydroxychloroquine (HCQ), and leflunomide (LEF). Nineteen pts who received parenteral gold in combination with ADA were excluded from this analysis. Baseline demographics and disease characteristics were summarized across csDMARD groups. 20/50/70% improvement in American College of Rheumatology (ACR) response criteria were assessed for each subgroup. Other clinical and functional endpoints were assessed using ANCOVA within subgroups as the least square (LS) means of the mean change from baseline to wk 24. Adverse events (AEs) were monitored throughout. Results: Of the 290 pts randomized to receive ADA, 237 (82%) received ≥1 csDMARD [174 (60%) and 63 (22%) received ADA in combination with 1 and ≥2 csDMARDs, respectively]. Of the 63 pts who received ≥2 csDMARDs in combination with ADA, 55 (87%) received concomitant MTX therapy. Similarly, most of the pts receiving ADA in combination with a single csDMARD received MTX [114 (66%)], while 60 pts received ADA in combination with a single non-MTX csDMARD. Pts receiving non-MTX csDMARDs were slightly younger, on average, than those receiving MTX (mean age: 51.4 vs 56.4 years), but demonstrated slightly higher mean HAQ-DI (1.37 vs 1.26) and CRP (2.4 vs 1.3) at baseline. Following 6 months of combination therapy, pts receiving ADA+MTX experienced numerically better clinical and functional outcomes to pts receiving ADA+non-MTX csDMARDs (Table). The lower response in the non-MTX DMARD group appeared to be driven by pts receiving LEF, who tended to experience lower levels of response in combination with ADA. Overall, frequencies of AEs were similar between combination therapy with MTX and non-MTX csDMARDs (∼90% in both groups). Serious AEs were observed in 10% of pts receiving non-MTX csDMARDs and 5% of pts receiving MTX. A total of 42% in the non-MTX csDMARD and 60% in the MTX group experienced infections during the course of the study. There were 3 serious infections, all occurring in the MTX group. Conclusions: MTX administered in combination with biologics, like ADA, leads to superior outcomes vs monotherapy. For pts who can't tolerate MTX, non-MTX csDMARDs, specifically HCQ and SSZ but not LEF, may be good alternatives, as outcomes were largely comparable with those of pts receiving MTX when combined with ADA. The limited sample size examined in this analysis should be confirmed in a larger pt population. References: Furst DE, et al. J Rheum 2003;30(12):2563–71. Acknowledgements: AbbVie: study sponsor, contributed to design, data collection, analysis, interpretation, and abstract writing, review, and approval. Medical writing: Ben Wolfe of AbbVie. Disclosure of Interest: E. Keystone Grant/research support from: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Centocor, F Hoffmann-LaRoche, Genentech, Genzyme, Merck, Novartis, Nycomed, Pfizer, UCB, Consultant for: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Centocor, F Hoffmann-LaRoche, Genentech, Genzyme, Merck, Novartis, Nycomed, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, AstraZeneca, Biotest, Bristol-Myers Squibb, Centocor, F Hoffmann-LaRoche, Genentech, Genzyme, Merck, Novartis, Nycomed, Pfizer, UCB, J. Suboticki Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., J. Griffith Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., Y. Zhang Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., J. Kremer Shareholder of: Corrona, LLC, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Regeneron, Sanofi, Pfizer, Employee of: Corrona, LLC